Quantification of Nigella sativa oil (NSO) from biodegradable PLGA nanoparticles using FTIR spectroscopy - Doolaanea, Abd Almonem; Harun Ismail, Ahmad Fahmi; Mohamed, Farahidah (Academic Sciences, 2014)
Objective: Quantification of medicinal plant, N. sativa oil, in biodegradable nanoparticles fabricated from PLGA and chitosan was impossible due to the difficulty in the oil extraction-partition method of which the nanoparticle did not dissolve in any solvent. Methods: FTIR method was developed to quantify the loading efficiency of NSO from the intact nanoparticles without the need to solubilise the nanoparticles and extract the NSO thereafter. Beer-Lambert law was applied in the quantification following selection of a few wave number combinations. Results: The method exhibited linearity in the range NSO/PLGA=5-150% with RIKOP Sdn. Bhd., Pilot Plant Pharmaceutical Manufacturing, Faculty of Pharmacy, IIUM, 25200 Kuantan, Malaysia. Email: farahidah@iium.edumy. 2 Keywords: Nigella sativa, FTIR, Loading efficiency, PLGA, Chitosan, Nanoparticle. =0.9911, RSD=1.68%, LOD=0.89% and LOQ=2.68%. NSO-PLGA nanoparticles revealed complete encapsulation of NSO (loading efficiency=101.5±2.2%) while chitosan-NSO-PLGA nanoparticle showed lower loading efficiency (84.5±1.7%) due to presence of the hydrophilic polymer, i. e. chitosan. This method is fast and easy to apply and does not require sample processing. The method will help to accelerate and improve routine characterisation of NSO nanoparticles during development and optimisation stage.